Evaluasi Sistem Pengendalian Intern Terhadap Prosedur Penjualan Tunai, Kredit, Konsinyasi dan Penerimaan Kas Pada PT. BESTARI BUANA MURNI Cabang Pekanbaru - Sri Rahmayanti; Resiyani Resiyani (Akuntansi & Ekonomika, 2019)
The purpose of this study is to evaluate the internal control system of the cash sales process, credit, consignment and cash receipt at PT. Bestari Buana Pure Branch Pekanbaru. Data were collected by observation, documentation and interview method. The data analysis used in this research is qualitative analysis which is aimed at whether the application of internal control system has according to the theory study, and quantitative analysis by testing the related documents using Attribute Sampling model of Stop Or Go Sampling. Based on the evaluation that has been done, the results of qualitative analysis of the questionnaire answers show that not in accordance with the study of theory, but has been adjusted to existing conditions in the company it is seen from the quality of employees in accordance with the responsibilities not in accordance with the existing SOP. While the quantitative analysis in conducting the control testing using the Stop Or Go Sampling model obtained the examination results that AUPL of 5% and DUPL of 5%, which means AUPL = DUPL so it can be concluded that the company's internal control system is effective.